2014
DOI: 10.4161/chan.28146
|View full text |Cite
|
Sign up to set email alerts
|

Exon 11 skipping ofSCN10Acoding for voltage-gated sodium channels in dorsal root ganglia

Abstract: (2014) Exon 11 skipping of SCN10A coding for voltage-gated sodium channels in dorsal root ganglia, Channels, 8:3,[210][211][212][213][214][215]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…In several mammals DRG neurons, alternative splicing of Na V α-subunit genes has been detected, resulting in the expression of multiple proteins. However, the functional significance of this process has not been completely elucidated ( Dietrich et al, 1998 ; Schirmeyer et al, 2014 ). Some variants seem to lead to subunits showing redundant or no obvious pharmacological and/or functional differences, compared with the wild-type subunit ( Schirmeyer et al, 2014 ).…”
Section: Voltage-gated Sodium Channels Expressed In Drg Neuronsmentioning
confidence: 99%
See 1 more Smart Citation
“…In several mammals DRG neurons, alternative splicing of Na V α-subunit genes has been detected, resulting in the expression of multiple proteins. However, the functional significance of this process has not been completely elucidated ( Dietrich et al, 1998 ; Schirmeyer et al, 2014 ). Some variants seem to lead to subunits showing redundant or no obvious pharmacological and/or functional differences, compared with the wild-type subunit ( Schirmeyer et al, 2014 ).…”
Section: Voltage-gated Sodium Channels Expressed In Drg Neuronsmentioning
confidence: 99%
“…However, the functional significance of this process has not been completely elucidated ( Dietrich et al, 1998 ; Schirmeyer et al, 2014 ). Some variants seem to lead to subunits showing redundant or no obvious pharmacological and/or functional differences, compared with the wild-type subunit ( Schirmeyer et al, 2014 ). However, different pharmacological and functional properties between variant and wild-type subunits are evidenced in the literature, such as their sensitivity to drugs/toxins ( Dietrich et al, 1998 ; Tan et al, 2002 ; Thompson et al, 2011 ; Boullot et al, 2017 ), their functional specificity regarding tissue/cell localization ( Song et al, 2004 ), and their involvement in membrane excitability via the regulation of translational repression ( Lin and Baines, 2015 ).…”
Section: Voltage-gated Sodium Channels Expressed In Drg Neuronsmentioning
confidence: 99%
“…One could hypothesize, therefore, that inflammation may decrease nociceptive neuronal excitability through Na v downregulation. However, Na v 1.7, as well as other Na v isoforms, can undergo alternative splicing, with each splice variant possessing distinct biochemical and pharmacological properties ( Schaller et al, 1992 ; Plummer et al, 1997 ; Dietrich et al, 1998 ; Schirmeyer et al, 2014 ). It was previously shown that a particular Na v 1.7 splice variant, Na v 1.7 11S, was upregulated and responsible for pain hypersensitivity in animal models of neuropathic pain ( Raymond et al, 2004 ).…”
Section: Protein Kinasesmentioning
confidence: 99%